Survey on finger-vein segmentation and authentication - Kharabe, Shwetambari; Nalini, C. (International Journal of Engineering and Technology, 2017)
Exploding growth in the field of electronic information technology, the finger vein authentication technique plays a vibrant role for personal identification and verification. In recent era, this technique is gaining popularity, as it provides a high security and convenience approach for personal authentication. Vein biometrics is an emerging methodologycomparing to other systems, due to its strengths of low forgery risk, aliveness detection and stableness over long period of time. Literatures published based on different techniques used forand authentication process are described and evaluated in this paper. These processes hadgained an outstanding promise in variety of applications and much attention among researchers to provide combine accuracy, universality and cost efficiency. This paper in brief, reviews various approaches used for finger vein segmentation and feature extraction. The reviews are based on finger vein basic principles, image acquisition methodology, pre-processing functions, segmentation, feature extraction,classification, matching and identification procedures, which are analyzed scientifically, thoroughly and comprehensively.Based on the analysis, the ideal process and procedure is identified, which will be an idyllic solution for finger vein authentication.